Deconstruction of Historical Facts In The Film ‘Anne Boleyn’ (2021) - Imamah, Fitria Habibatul; Mumtaz, Rafida (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The film Anne Boleyn (2021) recounts the historical narrative focusing on the tragic final years of Anne Boleyn, the Queen of England, from 1533 to 1536. However, controversy arose due to the inclusion of several black actors in roles deemed inconsistent with an accurate representation of a medieval-themed film portraying a non-fictional historical figure. This research aims to unveil the deconstruction strategies applied to historical facts in the 'Anne Boleyn' (2021). Data were gathered from literature and the film, and the analysis employed Derrida's textual deconstruction theory. The findings reveal film presents a narrative of deconstruction primarily through the practice of blackwashing, by casting a Black actress to portray the historically White figure of Anne Boleyn. This illustrates deconstructive elements characterized by fluidity in describing characters in an attempt to reinterpret history and expand interpretations of the past. Moreover, this narrative is not devoid of efforts to enhance the visibility of black representation in the film industry, particularly within Hollywood cinema.